Investigating the Stress Management Status in Middle-Aged Women in Bushehr based on a Transtheoretical Model - Nasrin Keshavarzi; Marzieh Mahmoodi; Homamodin Javadzade; Mahnoush Reisi (Hamadan University of Medical Sciences, 2021)
Aims: The present study aimed to investigate the relationship between self-efficacy, decision-making balance, and change processes with stress management in middle-aged women. Instrument & Methods: This cross-sectional study was performed in 2019 on 600 middle-aged women covered by Bushehr Comprehensive Health Services Centers. The method of sampling was stratified. Data was gathered by demographic questionnaire and TTM based questionnaire, including self-efficacy, decisional balance (perceived barriers and benefits), processes of change, and stage of changes. Data were analyzed using ANOVA and Tukey post hoc test in SPSS 20 software. Findings: The lowest and highest mean stress management scores were in the women in pre-contemplation (13.64±3.79) and maintenance (22.58±4.10), respectively. The mean score of self-efficacy in the women during the stages of change from pre-contemplation (15.71±6.80) to maintenance (33.06±5.09) was upward, and this average score in the stages of pre-contemplation, contemplation, and preparation was significantly lower than the stages of action and maintenance (p<0.001). Regarding processes of change, consciousness-raising, dramatic relief, environmental reevaluation, self-evaluation, social liberation, self-liberation, stimulus control, counter conditioning, helping relationships, and reinforcement management are significantly lower pre-contemplation and contemplation than action and maintenance (p<0.001). Conclusion: The results indicate the importance of TTM constructs in advancing individuals to higher levels of change. Based on this, it is recommended to design and implement educational interventions based on TTM to improve stress management behaviors.